Interpersonal Relations, Work Performance and Competence on Employee Performance - Syardiansah M.M.; Dhian Rosalina; Tami Silvi Afanin (Manajemen Bisnis, 2023)
This study aims to determine the effect of interpersonal relationships, work performance and competence on employee performanceat the Office of Women's Empowerment, Child Protection, Population Control and Family Planning in Langsa City. The method used in sampling was nonprobability sampling with saturated sampling technique and the number of samples in this study were 31 respondents. Data analysis in this study used the t test, F test and the coefficient of determination. The results showed that partially the interpersonal relationship variable has a positive and significant effect on employee performance. Work performance variable has a positive but not significant effect on employee performance. And competence has a positive but not significant effect on employee performance. Simultaneously interpersonal relationships, work performance and competence have a positive but not significant effect on employeeperformance. The results of the resulting multiple linear regression equation, it can be concluded that the interpersonal relationship variable has a positive influence on employee performance of 0.468X1. The work performance variable has a positive influence on employee performance of 0.043X2. And competency variables have a positive influence on employee performance of 0.153X3. Of the three independent variables that exist, the one that has the greatest positive influence on employee performance is the interpersonal relationship variable. From the results of the determination coefficient test it can be explained that 12.2% of the interpersonal relations variable, work performance and competency can explain the performance variable